Fixed-dose versus height and weight-adjusted dose of intrathecal 0.5% hyperbaric bupivacaine in elective cesarean section: A comparative study - K.C., Kiran Kumar; Shrestha, Amir Babu; Shrestha, Sangeeta (Journal of Society of Anesthesiologists of Nepal, 2020)
Background: Spinal anesthesia is the preferred anesthetic technique for cesarean deliveries. But there is a dosage dilemma regarding block to the desired level and preventing hypotension. We aim to study effects of fixed dose with height and weight-adjusted dose of intrathecal 0.5% hyperbaric bupivacaine during elective cesarean section. Methods: Eighty-eight singleton term parturients were enrolled and divided into two groups, Group FD (Fixed Dose) and CD (Calculated Dose) in this prospective, double-blind, randomized controlled trial. Group FD received 2.2 ml and CD received a height and weight adjusted calculated dose based on Harten's chart. Hemodynamic changes, onset time to sensory block to T6, maximum block in 20 minutes, and adverse effects were compared. Results: There was a significant reduction in median drug dosage of 11mg in FD versus 9 mg in CD group. The decrease in the MAP was less in group CD (14.5±2.98) mmHg compared to (17.6±4.66) mmHg in group FD (P= 0.03). The median onset time of spinal block to T6 in group FD of 2 minutes with IQR (2-3) was faster than Group CD 4 minutes with IQR (3-5). The spinal block extended above T4 in the larger number of parturients 23 (52 %) in Group FD than in three (6.8%) in group CD (p<0.05). Significantly larger number 20 (45.45 %) in group FD developed hypotension than seven (15.9 %) in Group CD. Bradycardia and vomiting were also found in group FD. Conclusions: This calculated dose provided the desired level of the spinal block and also restricted spinal block level with a distinct advantage of less hypotension.